Early growth and abdominal fatness in adult life. Issue 3 (June 1992) - Law, C M; Barker, D J; Osmond, C; Fall, C H; Simmonds, S J
Abstract : STUDY OBJECTIVE--The aim was to determine whether abdominal fatness in adult men is associated with retarded growth in fetal life and infancy. DESIGN--This was a follow up study of (1) men born during 1920-30 whose birthweights and weights at one year were recorded at the time by health visitors; and (2) men born during 1935-43 whose size at birth was measured in detail. The main outcome measure was the ratio of waist circumference to hip girth. SETTING--Hertfordshire and Preston, England. SUBJECTS--Subjects were 845 men born in east Hertfordshire who still live there; and 239 men born in Preston who still live in or close to the city. MAIN RESULTS--After allowing for body mass index, mean waist to hip ratio fell with increasing birthweight and rose as the ratio of placental weight to birthweight increased. These trends were independent of duration of gestation and therefore reflected retarded fetal growth. Waist to hip ratio also fell with increasing weight at one year. All these trends were independent of adult height, alcohol consumption, smoking, social class, and age. CONCLUSIONS--The tendency to store fat abdominally, which is known to increase the risk of cardiovascular disease and diabetes independently of obesity, may be a persisting response to adverse conditions and growth failure in fetal life and infancy.